Apuntes fenomenológicos sobre el perdón. Conversaciones entre la fenomenología de Merleau-Ponty y el libro Los rendidos de José Carlos Agüero - Mansilla, Katherine (2015)
This paper seeks to show the proximity between the phenomenologicalreflection that Merleau-Ponty presents in the article “The War Has Taken Place” (1945), and the stories of Jose Carlos Agüero, in his book, Los rendidos (The Surrendered) (2015). From a phenomenological perspective (pre-reflective), both authors describe the experience of pain, shame and forgiveness as the pursuit of freedom and justice. The text is divided into two parts. In the first part, we present discourses of justice which were established after the Peruvian armed conflict (1980-2000) and the need of exercising the phenomenological “epochè” in order to describe the feelings of terror and shame that underlie as background of this shared experience. In the second part, supported by Merleau Ponty’s concepts of intersubjectivity and historicity, we define freedom as the pursuit of justice, which can only be understood at the primordialaction of being in relation with others, from which we give meaning to the past.